(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE To determine the frequency of hypoglycemia and in-hospital mortality in children presenting with severe acute malnutrition at the Nutrition Stabilization Center of a tertiary care hospital in Larkana. METHODOLOGY A descriptive cross-sectional study was undertaken at the Department of Paediatrics, Shaheed Mohtarma Benazir Bhutto Medical University (SMBBMU), Larkana, enrolling 117 children, aged 6 months to 5 years, either gender, who were present with severe acute malnutrition for at least two weeks to assess hypoglycemia and in-hospital mortality. Data was analyzed by SPSS version RESULTS The mean ± standard deviation of the age was noted as 24.68 ± 13.75 months. Out of 117 children presented severe acute malnutrition, 54.7% were males and 45.3% were females. Hypoglycemia was noted in 19.65% patients and in-hospital mortality was noted in 60.9% of children. CONCLUSION This study highlights the strong association between hypoglycemia and in-hospital mortality in children with severe acute malnutrition (SAM). Risk was greater in younger and lower BMI children, suggesting the importance for early recognition and intervention. Providing routine blood glucose monitoring, appropriate treatment and total nutritional rehabilitation may lead to better survival rates. Mortality can be further decreased by strengthening hospital-based stabilization programs and training of hypoglycemia management of healthcare providers.